The Effect of Complex Exercises Using the Strategy of Pressure Game to Develop the Energy Expended for the Heart and the Speed of the Skilled Performance of the Football Players - Nabhan Hamid Ahmed (Journal of Global Pharma Technology, 2018)
The aim of the research is to identify the effect of the combined exercises using the play method of the pressure to develop the energy released to the heart and the speed of the skill performance of football players. As for the sample of the research, it included the players of the club of 22 players and the Anbar Youth Club participating in the 2016 league championship Results of the study showed that there were significant differences between the results of the research in the post tests of the control group and experimental and for the benefit of the experimental group. The findings of the researchers that the exercises combined with play pressure has a positive effect on the sample research Follicular and through the conclusions were to reach the most important recommendations, including the adoption of complex exercises in the training units and in the special stage of preparation and in a high-intensity interval training and repetitive because of its role in the development of research variables.Keywords: Complex exercises, Strategy, Pressure game, Energy expended, Heart and football players.